Radiation therapy primes tumors for nanotherapeutic delivery via macrophage-mediated vascular bursts. - Miller, Miles A. (Sci Transl Med, 2017)
Efficient delivery of therapeutic nanoparticles (TNPs) to tumors is critical in improving efficacy, yet strategies that universally maximize tumoral targeting by TNP modification have been difficult to achieve in the clinic. Instead of focusing on TNP optimization, here we show that the tumor microenvironment itself can be therapeutically primed to facilitate accumulation of multiple clinically relevant TNPs. Building on the recent finding that tumor associated macrophages (TAM) can serve as nanoparticle drug depots, we demonstrate that local tumor irradiation substantially increases TAM relative to tumor cells, and thus TNP delivery. High-resolution intravital imaging reveals that following radiation, TAM primarily accumulate adjacent to microvasculature, elicit dynamic bursts of extravasation, and subsequently enhance drug uptake in neighboring tumor cells. TAM depletion eliminates otherwise beneficial radiation effects on TNP accumulation and efficacy, and controls with un-encapsulated drug show radiation effects are more pronounced with TNPs. Priming with combined radiation and cyclophosphamide enhances vascular bursting and tumoral TNP concentration, in some cases leading to a 6-fold increase of TNP accumulation in the tumor, reaching 6% of the injected dose per gram tissue (ID/g). Radiation therapy alters tumors for enhanced TNP delivery in a TAM-dependent fashion, and these observations have implications for the design of next-generation tumor targeted nanomaterials and clinical trials for adjuvant strategies.